Beyond clinical trials: real-world impact of immunotherapy on NSCLC in Jordan - Abu Hejleh, Taher; AlSawalha, Karim; Abdel Hafiz, Sufian; Al-Batsh, Tamer; Abu Hejleh, Roaa; Yaser, Sameer; Abu Jazar, Husam; Khader, Jamal; Alnsour, Anoud; Mohamad, Issa; Abdel Jalil, Riad; Abu-Shanab, Ahmad; et al. (Frontiers in Oncology, 2024)
Background: This study aims to evaluate real-world (rw) outcomes of immunotherapy (IO) for advanced stage NSCLC at King Hussein Cancer Center (KHCC) in Jordan. Methods: Advanced stage NSCLC patients who received IO at KHCC between 2017 and 2022 were included. The data were retrospectively collected. PFS and OS were estimated for patients with ECOG performance status (ECOG PS) 0-1. Cox regression analyzed predictors of OS in first-line (1L) IO, regardless of performance status. Results The total number of patients included was 244. Out of those, 160 (65%), 67 (28%), and 17 (7%) patients received IO as 1L, second-line (2L), or third-line or beyond (3L or beyond), respectively. The median age for all patients was 59 years. Male were 88%, and 77% were smokers. The median follow-up time was 12.5 months. The median PFS and OS for 1L IO were 7 [95% CI 5.8 – 10.3] and 11.8 [95% CI 8.8 – 14.4], months, respectively. In the first 3 months after starting 1L IO, 34/160 (21%) patients had died. For those who survived beyond 3 months after starting 1L IO, the median PFS and OS were 11.3 [95% CI 8.3 – 16.5] and 15.4 [95% CI 13.2 – 21] months, respectively. In the Cox regression model of 1L IO patients with any performance status, ECOG PS 2 was predictive of worse OS compared to ECOG PS 0-1 (p= 0.005). Conclusion This real-world study of advanced-stage NSCLC patients treated with immunotherapy at KHCC reveals outcomes that fall short of those anticipated from clinical trials. The inclusion of Middle Eastern patients in lung cancer trials is essential to ensure adequate representation of various ethnicities in clinical research.